2020
DOI: 10.1177/1369433219895915
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the mechanical and self-sensing behaviors of prestressed carbon fiber–reinforced polymer reinforced concrete composite structures

Abstract: A type of self-sensing prestressed carbon fiber–reinforced polymer reinforced concrete composite structure was proposed and studied, composed of reinforced concrete beam, prestressed carbon fiber–reinforced polymer plate, and long-gauge fiber Bragg grating sensors. The carbon fiber–reinforced polymer plate was prestressed and bonded to the bottom of the reinforced concrete beam. Two types of anchorage systems were compared and studied. The long-gauge fiber Bragg grating sensors were used as active elements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…El sistema de anclaje juega un papel vital en las estructuras reforzadas con PRF y se han desarrollado varios tipos de sistemas de anclaje, por lo cual el refuerzo en una placa de concreto armado es más eficaz debido a su mayor grosor, sin embargo, esto origina que sea difícil de fijarse en la placa de concreto armado [10] .…”
Section: Metodologíaunclassified
“…El sistema de anclaje juega un papel vital en las estructuras reforzadas con PRF y se han desarrollado varios tipos de sistemas de anclaje, por lo cual el refuerzo en una placa de concreto armado es más eficaz debido a su mayor grosor, sin embargo, esto origina que sea difícil de fijarse en la placa de concreto armado [10] .…”
Section: Metodologíaunclassified
“…34 Other fatigue experiments on prestressed concrete beams under multi-level incremental amplitude cyclic loading were conducted, and the method of predicting their fatigue life was also put forward to fulfill the study database of fatigue properties. 35 More recently, studies on damaged concrete beams and strengthened beams have shown that the fatigue life degrades dramatically on an increase of loading amplitude. 36,37 Furthermore, from the tests on RC beams under coupling action of hot-wet environment and variable amplitude overload, it is concluded that a relatively high load level exacerbates the crack propagation of tensile rebars, which results in earlier fracture of rebars and further failure of strengthened beams.…”
Section: Introductionmentioning
confidence: 99%
“…Based on fatigue tests of concrete beams under two‐stage variable amplitude cyclic loading, the predictive fatigue life was more accurate by the method of residual strength criterion rather than by original Miner damage rule 34 . Other fatigue experiments on prestressed concrete beams under multi‐level incremental amplitude cyclic loading were conducted, and the method of predicting their fatigue life was also put forward to fulfill the study database of fatigue properties 35 . More recently, studies on damaged concrete beams and strengthened beams have shown that the fatigue life degrades dramatically on an increase of loading amplitude 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…By including up to 1.5% more steel fibres, the mechanical properties can be improved. When compared to glass fibre-reinforced concrete, the inclusion of 1.5% steel wires produces better outcomes [10]. The concrete of grade M30 will produce 10% greater compressive strength after 28 days of curing by adding waste metal scrap as a reinforced fibres to the concrete.…”
mentioning
confidence: 99%